How to start a home-based landscaping business - Dell, Owen E. (Home-based business series., 2015)
Landscaping continues to be an in-demand business field for motivated entrepreneurs. This seventh edition includes updated information on business plans, managing both employees and paperwork, taxes, and in-depth discussions on the role social media can play in your successful landscaping business.